2017
DOI: 10.1186/s12864-017-3899-8
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of trans regulatory eQTL to cryptic genetic variation in C. elegans

Abstract: BackgroundCryptic genetic variation (CGV) is the hidden genetic variation that can be unlocked by perturbing normal conditions. CGV can drive the emergence of novel complex phenotypes through changes in gene expression. Although our theoretical understanding of CGV has thoroughly increased over the past decade, insight into polymorphic gene expression regulation underlying CGV is scarce. Here we investigated the transcriptional architecture of CGV in response to rapid temperature changes in the nematode Caenor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
159
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 370 publications
(178 citation statements)
references
References 58 publications
18
159
1
Order By: Relevance
“…Among the significant trans-eQTLs, we found 55% were stimuli-specific, suggesting that a larger number of trans-eQTLs are detectable only in the presence of specific stimuli. These observations are consistent with findings from other species such as Caenorhabditis elegans 37 and Saccharomyces cerevisiae 38 showing that environmental perturbation yields a higher number of trans-eQTLs compared to cis-eQTLs. Together, these results underscore the need to perturb primary cells with environmental stimuli to discover genotype-phenotype relationships in trans.…”
Section: Discussionsupporting
confidence: 91%
“…Among the significant trans-eQTLs, we found 55% were stimuli-specific, suggesting that a larger number of trans-eQTLs are detectable only in the presence of specific stimuli. These observations are consistent with findings from other species such as Caenorhabditis elegans 37 and Saccharomyces cerevisiae 38 showing that environmental perturbation yields a higher number of trans-eQTLs compared to cis-eQTLs. Together, these results underscore the need to perturb primary cells with environmental stimuli to discover genotype-phenotype relationships in trans.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, of differentially expressed genes affected by genotype, 32.6% have zero downstream SNPs, 20.3% have zero intronic SNPs, and 18.6% have zero SNPs in the coding sequence, also consistent with a major role of trans ‐regulatory control being responsible for the genotype dependence of differential expression. Consistent with this idea, C. elegans shows a predominant role of trans ‐regulatory control in genotype‐dependent differential expression to acute heat stress (Snoek et al, ).…”
Section: Resultsmentioning
confidence: 80%
“…In this context, extensive transcriptome analysis of the nematode Caenorhabditis elegans in response to heat shock and knock‐out mutation began with microarrays (Kim, Lund, & Kiraly, ), with more recent studies using recombinant inbred lines of wild strains to map polymorphic loci that contribute genotype‐dependent responses to temperature (Grishkevich et al, ; Li et al, ; Snoek et al, , ). For example, Li et al () found that among 496 detectable expression quantitative trait loci (eQTL), trans ‐eQTL were nearly eight times as likely as cis ‐eQTL to show genotype‐by‐temperature responses, with subsequent study reinforcing this pattern (Snoek et al, ). Moreover, eQTL are found disproportionately on SNP‐dense chromosome arms in C. elegans (Rockman, Skrovanek, & Kruglyak, ).…”
Section: Introductionmentioning
confidence: 99%
“…If epistasis is systematically suppressive Hansen 2013), then the effects of isolated variants will routinely exceed their effects in their native genetic background. Such a pattern has been observed repeatedly in laboratory mice (Shao et al 2008;Tyler et al 2016), and several experiments have pointed to large stores of normally cryptic epistatic variation in C. elegans that can be exposed by genetic perturbations (Paaby et al 2015;Snoek et al 2017;Sterken et al 2017). Whether by repulsion-phase additive effects or tightly linked epistatic variants, C. elegans harbors a store of variation beyond that exposed by ordinary segregation.…”
Section: Discussionmentioning
confidence: 77%